Preparation of high quality, single domain BaFe12O19 particles by the citrate sol-gel combustion route with an initial Fe/Ba molar ratio of 4 - SOZERI, H.; Durmus, ZEHRA; Baykal, A.; UYSAL, E. (My University, 2012)
BaFe12O19 particles have been synthesized by citrate sol-gel combustion route in a wide temperature range between 800 and 1200 degrees C with initial Fe/Ba molar ratios between 12 and 2. Structural, morphological and magnetic properties of the powders have been investigated by XRD, FT-IR, SEM and magnetization measurements. It was observed that both coercivity and specific saturation magnetization increase with annealing at temperatures up to 1100 degrees C, where a transition from single to multi domain structure occurs. To prevent formation of the hematite phase (alpha-Fe2O3), samples with different Fe/Ba molar ratios between 12 and 2 have been prepared and an intermediate phase, BaFe2O4, which may occur in Ba-rich samples has been removed by etching the powders in diluted hydrochloric acid. In this way, it was shown that single domain barium hexaferrite particles having high saturation magnetization, close to the theoretical value, and high coercivity can be synthesized with the initial Fe/Ba molar ratio of 4 in the sol-gel method. The chemical composition of this sample was determined as BaFe11.80O19.45 by the EDS analysis and Ba1.05Fe11.54O18.4 using an ICP-MS device. Both are very close to the theoretical formula. (c) 2012 Elsevier B.V. All rights reserved.